Consumer behaviour of Islamic home financing: Investigating its determinants from the theory of Islamic consumer behaviour. Issue 4 (13th November 2017) - Amin, Hanudin
Abstract : Purpose: The purpose of this study is to examine the contributing factors that affect consumer behaviour of Islamic home financing in Malaysia. The effects of perceived religiosity on property, perceived Islamic debt principle and perceived maqasid on homeownership on consumer behaviour are examined. Furthermore, the effects of perceived religiosity and consumer behaviour on religious satisfaction are also investigated. Design/methodology/approach: Using the theory of Islamic consumer behaviour (T i CB) as a baseline theory identified from the literature, this study proposes a conceptual model of consumer behaviour of Islamic home financing in Malaysia. Data from the 205 usable questionnaires are analysed using partial least squares (PLS). Findings: The PLS results suggest that perceived religiosity on property, perceived Islamic debt principle and perceived maqasid on homeownership are instrumental in determining consumer behaviour, thus revealing these factors as "Islamic factors" that represent the T i CB. Furthermore, the effect of consumer behaviour on religious satisfaction is also significant, implying that good behaviour makes people happier – seeking pleasure for doing well that is blessed and approved by Allah (S.W.T). Research limitations/implications: Two limitations are available for future studies. First, this study included only Malaysians in East Malaysia, suggesting that further testing of the proposed model should be conducted across different geographies to determine the generalisability of this study's findings. Second, this study's contributions are narrowed down to the factors examined. These limitations, however, provide directions for further future research. Practical implications: The results provide directions to bank managers to effectively manage Islamic home financing services for the benefit of their customers. Islamic home financing products tend to be used by consumers if the patronage factors investigated are considered more profoundly. Originality/value: This study examines the behaviour of consumers of Islamic home financing using the proposed framework derived from T i CB.